A CASE STUDY OF LEARNING MATHEMATICS VIA SELF-DIRECTED INTERACTIVE POWERPOINT - Low Chee Soon; Yap Oi Jiong; Lim Chien Sheng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
PowerPoint has been a popular presentation tool for conveying learning materials in educational institutions. While slides and points simply move on clicks, students may find presentation too quickly to absorb, digest and reflect on its contents. This study is an exploratory attempt to turn PowerPoint slides into an interactive, self-paced and self-directed learning platform (iPP) designed for learning to solve equations and inequalities involving absolute values. The purpose of the study was aimed at a quick initial assessment of the design effectiveness particularly for pedagogic improvement. The purposive sample involved an A-Level student who voluntarily sat for a pretest and interacted with the PowerPoint slides before attempting a posttest. The participant’s interaction with the iPP was both observed and video-recorded, and the solutions to the pretest and posttest qualitatively compared. In particular, the fine-grained analysis of the participant’s interaction with the iPP, which offers the opportunity to attempt tasks, access worked solutions, learn concepts and explore reasoning, may explain the participant’s enhanced performance particularly in solving inequalities. Nonetheless, the observations on the participant-slide interactivity led to some pedagogical insights as to how interactive slides could meet a better design for more effective learning. It is concluded that interactive PowerPoint slides which contain pedagogical and resourceful contents and allow for autonomous navigation may support mathematics learning.